Staging martyrdom in the trial of El Niño de La Guardia. Issue 1 (2nd January 2018) - Duque, Adriano
ABSTRACT: The ritual sacrifice of the child of La Guardia in 1491 can be seen as a lens to examine anti-Jewish sentiment in fifteenth-century Castile. This article argues that the deposition made by the Jews of La Guardia hinged on a triple set of interpretations that tended to represent the sacrifice of the child of La Guardia as a mockery of pig-slaughtering sacrifices but also as a representation of Jewish medical malpractice. The article further connects the representation of the child of La Guardia with the image of the crucified monk and with the " Vueltas de San Antón ", a festival in which a child was crowned as the king of the pigs.